Peptide solubility, structure and charge position effect on adsorption by aluminium hydroxide (2006)
Solubility, structure and position of charges in a peptide antigen sequence can be mentioned as being amongst the basic features of adsorption. In order to study their effect on adsorption, seven analogue series were synthesized from a MSP-1 peptide sequence by systematically replacing each one of the positions in the peptide sequence by aspartic acid, glutamic acid, serine, alanine, asparagine, glutamine or lysine. Such modifications in analogue peptide sequences showed a non-regular tendency regarding solubility and adsorption data. Aspartic acid and Glutamic acid analogue series showed great improvements in adsorption, especially in peptides where Lysine in position 6 and Arginine in position 13 were replaced. Solubility of position 5 analogue was greater than the position 6 analogue in Aspartic acid series; however, the position 6 analogue showed best adsorption results whilst the Aspartic acid in position 5 analogue showed no adsorption in the same conditions. Nuclear Magnetic Resonance structural analysis revealed differences in the -helical structureextension between these analogues. The Aspartic acid in position 6, located in the polar side of the helix, may allow this analogueto fit better onto the adsorption regions suggesting that the local electrostatic charge is responsible for this behavior.